Student Perspectives on improving mental health support Services at university. Issue 1 (8th February 2021) - Priestley, Michael; Broglia, Emma; Hughes, Gareth; Spanner, Leigh
Abstract: Drawing on thematic analysis of six student co‐creation panels, conducted during the Student Minds University Mental Health Charter consultations, this paper elucidates students' perspectives and proposals regarding the current issues and challenges around university student mental health and well‐being support services. In particular, panels identified existing challenges and opportunities to improve support service access, strategy, and delivery. The panels generated a series of recommendations aimed to establish a clear, coordinated, and strategic approach to delivering accessible and inclusive student mental health support services that are responsive to the diverse needs of the whole student population. Significantly, the student panels situated service reforms within a 'whole university approach' entailing holistic structural and cultural change to the university environment, in order to enrich student mental health and well‐being and reduce demand on services. The findings of this paper can both reaffirm and specify the principles of good practice propounded by the University Mental Health Charter from a student perspective.